Infotainment Media Forms Hybrid Genres in the American and Romanian Televisual Press - BOGDAN (Nicoară), Rada Daniela (2021)
The hypothesis of this thesis is that the 21st century has redefinedjournalism by the subjectivity with which several topics of national interestare addressed. Following the American model and considering the era ofglobalization we live in, the initial principles of journalism are considerablylosing their importance, converging to entertainment. We shall approach theproblem of genre hybridization within the televisual press, insisting upon theemergent forms proposed by some American (The Daily Show, Last WeekTonight, The Late Night and Late Show) and Romanian shows (România de la Ala Z, Starea Nației, Lumea lui Banciu and În gura presei. Hence, all these casestudies plan to emphasize the conjunction of some serious and non-seriousgenres, in an attempt to define the variable forms of an “ongoing journalisticgenre” (infotainment).